Model Evaluasi Perencanaan Pembangunan di Sumatera Utara - Muhammad Arifin Nasution; Nurman Achmad (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
The purpose of this study is the realization of the performance achievements of program plans and regional priority activities that have been targeted in the North Sumatra Province Regional Work Plan (RKPD) 2019. To evaluate public policies, it is necessary to measure the success of public programs and policies (effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy) Accuracy indicators are the most successful to be used in measuring the level of consistency. Meanwhile, the success of the Equity indicator is very difficult to measure, considering that the amount of the budget for programs and activities is not the same. The research design used in this study is a combination of qualitative and quantitative approaches with a dominant-less dominant design model. The results of the data obtained were carried out using descriptive-analytical methods. The results of the study showed that by looking at some of the standards used to evaluate the results of the North Sumatra province's RKPD Implementation in 2019 it showed a very good value. Evaluation of the results of regional development plans aims to achieve conformity between regional development achievements and established performance indicators. The performance indicators in question are performance indicators determined at the national, provincial, and district/city levels. So far, the measurement used by BAPPEDA of North Sumatra Province in evaluating development planning is only based on budget realization.